2009
DOI: 10.3109/01421590903390593
|View full text |Cite
|
Sign up to set email alerts
|

Personality testing may improve resident selection in anesthesiology programs

Abstract: Background: Current methods of selecting future residents for anesthesiology training programs do not adequately distinguish those who will succeed from the pool of seemingly well-qualified applicants. Some residents, despite high exam scores, may struggle in the operating room (OR) in stressful situations. Aims: This study examined whether specific neuropsychological and personality measures can distinguish high competency residents from low-competency residents to aid in resident selection. Methods: Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
(16 reference statements)
1
18
0
Order By: Relevance
“…These findings are expected and may be seen as analogous to the findings of a study performed within an anesthesiology training program evaluating 25 anesthesiology residents [22]. In that study, high-competency residents showed significantly greater cooperation, self-efficacy, and adventurousness and less neuroticism, anxiety, anger, and vulnerability than low-competency residents, but the two groups did not differ in terms of fine motor dexterity, executive functioning, processing speed, or attention.…”
Section: Discussionsupporting
confidence: 69%
“…These findings are expected and may be seen as analogous to the findings of a study performed within an anesthesiology training program evaluating 25 anesthesiology residents [22]. In that study, high-competency residents showed significantly greater cooperation, self-efficacy, and adventurousness and less neuroticism, anxiety, anger, and vulnerability than low-competency residents, but the two groups did not differ in terms of fine motor dexterity, executive functioning, processing speed, or attention.…”
Section: Discussionsupporting
confidence: 69%
“…Personality testing, task-based questions related to the responsibilities of a resident, evaluation under simulated stressful conditions, and character assessment are all important facets of applicant review that complement each other, and some have been formally investigated in selecting residents. 8,[24][25][26] Ideally, a method can be developed that incorporates all of these things to allow for an accurate judgment of a potential resident's performance in a given program.…”
Section: Commentmentioning
confidence: 99%
“…Eight studies explored the use of personality [99][100][101][102][103] or emotional intelligence [104][105][106] testing as part of resident selection. Use of the Myers-Briggs personality inventory for interviewers and applicants demonstrated that clinician faculty ranked candidates more favorably when they shared certain personality styles.…”
Section: Personality Testingmentioning
confidence: 99%